Rhetorical Style Across Cultures: An Analysis of Metadiscourse Markers in Academic Writing of Thai and Malaysian Students (LSP International Journal, 2019)
It is believed that students from different societies and cultural background have their own preferred rhetorical style of interaction. In writing, such distinctive preference is usually exhibited through the use of linguistic features, of which metadiscourse (MD) markers are considered as one of the signposts to the interpretation of writing style preferences. This study aims to investigate the use of interactional metadiscourse (MD) features and its relevance to the rhetorical style preferences in academic writing of Thai and Malaysian master’s students. Using Hyland’s (2005) taxonomy, their thesis discussions were manually analysed in terms of interactional MD markers to determine their frequency of occurrence and to relate the results to the rhetorical styles of writing preferred by each group of students. The analysis revealed that of all five types of interactional MD features, hedges were the most frequently used device followed respectively by boosters, attitude markers, engagement marker and self-mention. In terms of the rhetorical style of writing, the frequency of MD features suggests that tentative and indirect statements, reader-responsibility, distant-relationship between writer and readers, and less writer-involvement in the texts were the preferred rhetorical styles of interaction of both Thai and Malaysian students. The writing conventions and rhetorical styles of the students can be explained from a sociocultural point of view that they are relevant to the oriental style of interaction from which both groups of students originated. The study draws attention to the pedagogical implications that students in Thai and Malaysia should be given more instructional focus on how to utilize MD features in making academic writing more persuasive and interactive.